Derivation and validation of a composite scoring system (SAVED2) for prediction of unfavorable modified Rankin scale score following intracerebral hemorrhage - Coleman, Craig I.; Concha, Mauricio; Koch, Bruce; Lovelace, Belinda; Christoph, Mary J.; Cohen, Alexander T. (Frontiers in Neurology, 2023)
Objective To develop a composite score for predicting functional outcome post–intracerebral hemorrhage (ICeH) using proxy measures that can be assessed retrospectively. Methods Data from the observational ERICH study were used to derive a composite score (SAVED2) to predict an unfavorable 90-day modified Rankin scale (mRS) score. Independent predictors of unfavorable mRS were identified via multivariable logistic regression and assigned score weights based on effect size. Area under the curve (AUC) was used to measure the score's discriminative ability. External validation was performed in the randomized ATACH-2 trial. Results There were 2,449 patients from ERICH with valid mRS data who survived to hospital discharge. Predictors associated with unfavorable 90-day mRS score and their corresponding point values were: age ≥70 years (odds ratio [OR], 3.8; 1-point); prior stroke (OR, 2.8; 1-point); need for ventilation (OR, 2.7; 1-point); extended hospital stay (OR, 2.7; 1-point); and non-home discharge location (OR, 5.3; 2-points). Incidence of unfavorable 90-day mRS increased with higher SAVED2 scores (P < 0.001); AUC in ERICH was 0.82 (95% CI, 0.80–0.84). External validation in ATACH-2 (n = 904) found an AUC of 0.74 (95% CI, 0.70–0.77). Conclusions Using data collected at hospital discharge, the SAVED2 score predicted unfavorable mRS in patients with ICeH.